Keragaman Sifat Anatomi Kayu Sengon dan Kemungkinan Penggunaannya sebagai Bahan Furniture - Sushardi; Bowo Woesono, Hastanto; Hadi, Didik Surya (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2022)
The development of modern industries has demanded ever-increasing usage requirements for wood products. The use of wood will be more effective and efficient if the properties of wood are known beforehand. This study aims to determine the anatomical diversity of sengon wood and its possible use as a raw material for furniture. This study used a randomized block design with Tukey's follow-up test. The factor used consisted of the radial direction of wood (wood near the skin and wood near the heart). Parameters observed were the proportion of fiber cells (%), the proportion of vessel cells (%), the proportion of parenchyma cells (%), and the proportion of radius cells (%). The results showed that the wood near the skin and near the heart of sengon had variations in the proportion of fiber cells, the proportion of vessel cells, the proportion of parenchyma cells and the proportion of radius cells. The average value of the anatomical diversity of sengon wood in the radial direction is the proportion of fiber cells 49.02 - 50.24 %, the proportion of vessel cells 23.22 - 24.23 %, the proportion of parenchyma cells 13.47 - 14.57 %, the proportion of finger cells finger 11.53 - 13.39 % and . Sengon wood can be used as furniture material for light buildings or for artificial boards because it has a high proportion of fibers.